Fishing-down within populations harms seed dispersal mutualism - Costa-Pereira, Raul [UNESP]; Correa, Sandra Bibiana; Galetti, Mauro [UNESP] (Wiley, 2018)
Large fish are often the most effective seed dispersers, but they are also the preferred target for fisheries. We recently started to comprehend the detrimental impacts of the extirpation of large frugivorous fish species on natural forest regeneration, but we lack a general understanding of how intraspecific size-selective harvest affects fish–fruit mutualism. Our literature review demonstrated that large individuals within populations positively affect diverse aspects of seed dispersal, from consuming a higher diversity of seeds to enhancing germination. Furthermore, we filled a research gap by studying how individual size variations within two small frugivorous fish species (<16 cm) affect seed dispersal in flooded savannas. Even within small-bodied species, large individuals swallow a higher number of intact seeds, but not necessarily a higher proportion. Overall, our results demonstrate the disproportional role of large-bodied individuals as key seed dispersers in flooded habitats. Consequently, fishing-down within both large- and small-bodied species can negatively affect seed dispersal and natural regeneration in overfished wetlands.
Keywords: body size; downsizing; floodplain; frugivory; ichthyochory; overfishing; Pantanal; size-selective harvesting